The effect of currency exchange on product costs and production locations in crane component manufacturing - Riihimäki, Magnus (My University, 2019)
Currency exchange rates have a central role when evaluating production costs and production locations. Studies in this field have historically focused on production cost formation on a factory level and logistical costs and many times left the effects of the currency exchange rate to less attention. Exchange rates form an essential cost factor if the profits are eaten up by the current situation in the monetary market. This study aims to connect these topics and attempts to give simple ways to control the risks associated with the currency exchange fluctuations. In addition, the main ingredient and cost factor in many industries: steel, is often times overlooked in previous studies. In the theoretical part of the study the focus is on the currency exchange rate fluctuations and prevention alongside risk management for this phenomenon. The price of steel is also examined because in addition to cost, it is one of the most influential factors in production location planning. The target is to find out the scale of the effects the exchange rates cause and to include the price of steel and its fluctuations in the production cost counting. The basic theories of Krugman (1979) about economic geography are also examined because comparative advantages in production are key concepts in locational decision-making. The main aim of this study is to evaluate components of a global crane manufacturer: Konecranes Ltd and their production costs and estimate the effects of exchange rate fluctuation on those components. Quantitative methods were used in assessing the available cost information and evaluation and two models were formed to describe the phenomenon. Data was gathered from the company’s own enterprise resource planning system: SAP and additional data that had been acquired outside the system. Qualitative methods were used when conducting multiple unstructured interviews that directed the study and helped to shape the research question. In the empirical part of the study different production costs from different factories for the same components were compared and historic development of the exchange rates were taken into consideration as the results were made comparable. Two models were created with three different imaginary factories in different countries to describe the phenomenon. Those models represented the possible magnitude of the exchange rates and the countering force of the steel price fluctuations. The effect could possibly be enough to consider changing manufacturing location decisions, but the situation can change profoundly rapidly in comparison to the time and effort that a change in manufacturing locations requires. The study found the overall possible magnitude of the effects of global currency exchange rate fluctuations and their effects on production costs.